The big kahuna [compact disc, unabridged] - Evanovich, Janet; Evanovich, Peter (Evanovich, Janet. Fox and O'Hare novels., 2019)
When unlikely partners FBI agent Kate O'Hare and con man Nicholas Fox investigate a missing Silicon Valley billionaire known as the Big Kahuna, they go undercover as a married couple in Paia, Maui, to find the man's son.